Hypertriglyceridemia is associated with stroke after non-cardiac, non-neurological surgery in the older patients: A nested case-control study - Chen, Chaojin; Wen, Qianyu; Ma, Chuzhou; Li, Xiaoyue; Huang, Tengchao; Ke, Jie; Gong, Chulian; Hei, Ziqing (Frontiers in Aging Neuroscience, 2022)
Introduction: Geriatric postoperative stroke is a rare but serious complication after surgery. The association between hypertriglyceridemia and postoperative stroke remains controversial, especially in older patients undergoing non-cardiac, non-neurological surgery. The study aims to address this clinical dilemma. Methods: We conducted a nested case-control study among 9601 aged patients undergoing non-cardiac non-neurological surgery from October 2015 to October 2021. A total of 22 positive cases were matched for the surgical type and time, to 88 control patients by a ratio of 1:4. The effect of hypertriglyceridemia on the occurrence of postoperative stroke within 30 days after surgery was estimated using conditional logistic regression analysis by adjusting to various potential confounders. Results: A total of 22 cases developed ischemia stroke after surgery, and compared with the non-stroke group, they had more postoperative ICU admission, longer postoperative hospitalization and higher total cost (all p < 0.05), and more patients were presenting with preoperative hypertriglyceridemia [8 (36.4%) vs. 15 (17.0%), p = 0.045]. There was a significant association between hypertriglyceridemia and postoperative stroke, with adjusted odds ratios of 6.618 (95% CI 1.286, 34.064) (p = 0.024). The above results remained robust in the sensitivity analyses. Conclusions: Among older patients undergoing non-cardiac and non-neurological surgery, hypertriglyceridemia was associated with significant increased risk of postoperative stroke.